2019
DOI: 10.1186/s13018-019-1430-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA TUG1 was upregulated in osteoporosis and regulates the proliferation and apoptosis of osteoclasts

Abstract: Background Long non-coding RNA (LncRNA) TUG1 plays critical roles in the development of human cancers. Its inhibition has been proved to participate in ankylosing spondylitis, which is an inverse pathological procedure of osteoporosis. In the present study, we aim to investigate the role of lncRNA TUG1 in ankylosing spondylitis. Materials and methods Expressions of lncRNA TUG1 in plasma of 98 patients with osteoporosis and 60 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…LncRNA has been con rmed to play a vital role in bone metabolism diseases. Han et al revealed that downregulation of lncRNA TUG1 effectively inhibited osteoclast proliferation and might serve as a potential target for the treatment of osteoporosis [16]. Shen et al reported that lncRNA HOTAIR was highly expressed in osteoporosis patients, which prevented osteogenic differentiation by regulating Wnt/βcatenin pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA has been con rmed to play a vital role in bone metabolism diseases. Han et al revealed that downregulation of lncRNA TUG1 effectively inhibited osteoclast proliferation and might serve as a potential target for the treatment of osteoporosis [16]. Shen et al reported that lncRNA HOTAIR was highly expressed in osteoporosis patients, which prevented osteogenic differentiation by regulating Wnt/βcatenin pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been shown to regulate osteoclastogenesis by regulating the expression of specific target mRNAs. In osteoporosis, the increased expression of lncRNA TUG1 can regulate the proliferation and apoptosis of osteoclasts through Pten [86]. During the formation of osteoclasts, the expression of lncRNA AK077216 was significantly up-regulated.…”
Section: Lncrna-mediated Mechanismsmentioning
confidence: 99%
“…lncRNA TUG1 (taurine-upregulated gene 1) is thought to be upregulated in osteoporosis. This theory is based on the fact that it is inhibited in ankylosing spondylitis, which is commonly thought of as an inverse pathological process to osteoporosis [ 67 ]. In the plasma of patients of both genders at various stages of osteoporosis, there was upregulation of lncRNA TUG1 [ 67 ].…”
Section: The Role Of Micro Rna (Mirna) and Long-non-coding Rna (Lnmentioning
confidence: 99%
“…This theory is based on the fact that it is inhibited in ankylosing spondylitis, which is commonly thought of as an inverse pathological process to osteoporosis [ 67 ]. In the plasma of patients of both genders at various stages of osteoporosis, there was upregulation of lncRNA TUG1 [ 67 ]. Although the mechanism of action of lncRNA TUG1 has not yet been elucidated, it is thought to sponge miR-204-5p to promote osteoblast differentiation [ 67 ].…”
Section: The Role Of Micro Rna (Mirna) and Long-non-coding Rna (Lnmentioning
confidence: 99%